1999
DOI: 10.1248/bpb.22.360
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Tetrandrine and Related Synthetic Compounds on Angiogenesis in Streptozotocin-Diabetic Rodents.

Abstract: Structure-activity relationships of tetrandrine, isolated from a Kampo medicine, Stephania tetrandrae S. MOORE (root), and related synthetic compounds, were investigated in in vitro fetal bovine serum (FBS)-stimulated angiogenesis of cultured choroids in streptozotocin-diabetic Wistar rats, and air-pouch granuloma angiogenesis in vivo in diabetic mice. Tetrandrine, KS-1-1 (6,7-dimethoxy-1-[[4-[5-(6,7-dimethoxy-2-methyl-1,2,3,4-tetrahydroiso quinolinyl)methyl-2-methoxy]phenoxy]benzyl]-2-methyl-1,2,3,4-tetrahyd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 1 publication
0
25
0
Order By: Relevance
“…24 Tetrandrine inhibits choroidal angiogenesis and air-pouch granuloma angiogenesis in diabetic rodents and fetal bovine serum-, IL-1a-, VEGF-or platelet-derived growth factor (PDGF)-BB-stimulated tube formation in vascular endothelial cells. 24 There are no previous reports on the effect of tetrandrine on angiogenesis in malignant tumors. Angiogenesis can promote tumor growth and increase the number of channels for tumor cell metastases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 Tetrandrine inhibits choroidal angiogenesis and air-pouch granuloma angiogenesis in diabetic rodents and fetal bovine serum-, IL-1a-, VEGF-or platelet-derived growth factor (PDGF)-BB-stimulated tube formation in vascular endothelial cells. 24 There are no previous reports on the effect of tetrandrine on angiogenesis in malignant tumors. Angiogenesis can promote tumor growth and increase the number of channels for tumor cell metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In Group D, 70% of the rats had longterm survival and the survival time of rats that ultimately died was 68 days longer. The survival rate of Group D rats was significantly higher than that of Groups A, B and C (Group D vs. Group A or B, 24 or 72 hr, the apoptosis fraction of the RT-2 glioma cells was analyzed using a flow-activated cell sorter (FACS). Each point is the average of 3 independent trials (9 determinations for each concentration) and presented as mean 6 standard deviation.…”
Section: Effect Of Tetrandrine On Subcutaneous Gliomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetrandrine have been demonstrated to inhibit lipid peroxidation and platelet aggregation and reduces ischemia/reperfusion injury (28)(29)(30) and tetrandrine suppressed T and B cells and inhibited the production of cytokines (29). It was reported that tetrandrine is cytotoxic to RT-2 glioma cells and it has antitumor effects on subcutaneous and intracerebral gliomas, and inhibits angiogenesis in subcutaneous gliomas (31)(32)(33)(34). Tetradine induced apoptosis by activating reactive oxygen species and repressing Akt activity in human hepatocellular carcinoma HCC cells (35,36).…”
Section: Introductionmentioning
confidence: 99%
“…4) Tetrandrine inhibits precapillary formation of vascular endothelial cells and neovascularization of cultured choroidal explants in STZ-diabetic rats, 8,9) but does not affect hyperglycemia in diabetic mice.…”
Section: )mentioning
confidence: 99%